Humanização e transcendência: o encontro do humano com o divino, à luz da psicologia transpessoal, pela visão de Ken Wilber - Candello, Maria Letícia (2008)
The dissertation s focus is the humanization and transcendence that is established when the human being meets the divine. The theoretical support is Ken Wilber s vision of transpersonal psychology. As a preamble, it covers human being concepts, humanism and humanization in its historical evolution, showing the philosofical thought building steps related to these themes since the mytological vision. The concern was to demonstrate that the basis of the transpersonal psychology and its transcendence vision were being built through the evolution process. At the postmodern condition, there is the lost of sense due to human being s, and society s fragmentation. Besides this lost, it appears the search for new ways for psyche s evolution that brings hope to recover the human. Finally, it demonstrates the hypothesis of human reconstruction throught humanization and transcendence process, at a postmodern condition, based on Wilber s transpersonal psychology conception that can be found in his and other authors s works whose focus is the human conscience and its evolutes stages